2018
DOI: 10.24132/acm.2018.385
|View full text |Cite
|
Sign up to set email alerts
|

On the level of computational model of a human skull: A comparative study

Abstract: In this study, different patient-specific computational models of the skull, which are often used in literature, were investigated, analysed and compared. The purpose of this study was to demonstrate the differences in computational model creation and results in case different computational models based on same computed tomography (CT) dataset are used. The selection of computational model directly influences the values of investigated parameters. The effort is to demonstrate, how the selection of the computat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This assumption presents a simplification as compared to the real materials. However, it is a rather standard practice for modeling the implants [2,12,36]. The HA thin layer has not been commonly modeled in cranial implantology, so samples with this layer were sprayed and analyzed to obtain relevant input values.…”
Section: Materials Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption presents a simplification as compared to the real materials. However, it is a rather standard practice for modeling the implants [2,12,36]. The HA thin layer has not been commonly modeled in cranial implantology, so samples with this layer were sprayed and analyzed to obtain relevant input values.…”
Section: Materials Modelmentioning
confidence: 99%
“…The force was applied to a small circular area in the center part of the implant (denoted as red regions in Fig 2C). All analyzed models were fixed at the bottom side of the modelled part of the cranium [36].…”
Section: Loads and Boundary Conditionsmentioning
confidence: 99%
“…The human neurocranium forms a three-layered composite consisting of two compact tables that enclose the cancellous diploë in a sandwich-like manner 4 . In contemporary finite element models, the diploë is either neglected or represented in an oversimplified manner due to the lacking or controversial material properties that are available in the scientific literature 5 . Previous research regarding the load-deformation behavior of the human neurocranium mainly focused on full-thickness composites 6 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Other skull models have been developed for particular studies, studying very specific subjects, different from the works mentioned above that comprise the entire head structure. Chamrad et al [ 33 ] reviewed different ways to model the human skull and concluded that the skull model must have both types of bone. Additionally, the case of cortical bone modeled with shell element-layers filled with solid elements that represent trabecular bone tissue, it was found to be less precise and feasible than modeling it with solid elements.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the case of cortical bone modeled with shell element-layers filled with solid elements that represent trabecular bone tissue, it was found to be less precise and feasible than modeling it with solid elements. Chamrad et al [ 33 ] also compared different cortical thicknesses, 1 and 2 mm, and better results were achieved with the thinner cortical layers. Nevertheless, the response might have been influenced by the simply linear-elastic material models employed.…”
Section: Introductionmentioning
confidence: 99%